Genetic diversity for yield components in sesame (Sesamum indicum L.) - Gadanya, Abdullahi Ibrahim [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The study on genetic diversity for yield components in sesame (Sesamum indicum L, Pedaliaceae family) was done at the Jaboticabal campus, in the Screen house and Molecular laboratory of Universidade Estadual Paulista, (Unesp) Brazil. This was aimed to elucidate the diversity among some sesame varieties (Sesamum indicum L) in Nigeria using agro-morphological parameters and Inter-simple sequence repeats (ISSR) molecular markers. Eight sesame varieties: NCRIBEN-01M, NCRIBEN-02M, NCRIBEN-04E, NCRIBEN-05E, Black seeded, E8, Gujarat, and Yandev-55 were planted in the screen house. Leaves were collected at 12 days after planting and processed for molecular evaluation. Furthermore, each variety were evaluated morphological agronomic parameters in screen house potted experiment the varieties varied in seed coat colour of four groups: black, brown, light brown, white and ovate leaf lobe in E8 variety. Plant height (cm) ranged from 96.4±1.1 to 144.3±2.0, days for 50% flowering and days to maturity ranged from 55±1.0 to 68±1.0 and 91±1.0 to 130±2.0 days respectively. Yield influencing parameters had ranges of 35±2.0 to 63±1.0 for capsule per plant, 52±2.0 to 76±2.0 for seed per capsule and 2.12±1.56 to 4.43±0.1 for 1000 seed weight (g). Principal components matrix revealed that the PC1, which accounted for the highest variability was mostly related to yield related traits like number of capsules plant', number of primary branches plant⁻¹ and 1000 seed weight. PC2 was dominated by growth related traits. Dissimilarity dendrogram of the studied sesame genotypes, established using Agglomerative clustering at 0.821 coefficient, revealed three clusters. These results showed variability in yield traits of these sesame varieties studied. Eleven ISSR primers were used for analysis eight different sesame -populations from Nigeria. The primers showed legible and reproducible genomic profiles. The 11 primers amplified 472 bands of which 228 (48.3 %) were polymorphic. PIC (Polymorphic Information Content) PIC in this study with 11 sesame genotypes varied from 0.330 to 0.50 an indication of the informativeness of ISSR markers as well as their relevance in discriminating the populations studied. There is therefore diversity among the sesame genotypes studied. Further studies on genetic diversity of Nigerian sesame accessions using ISSR markers using greater numbers of markers and genotypes will further unravel their degree of diversity is recommended

O estudo sobre a diversidade genética para componentes de rendimento em gergelim (Sesamum indicum L, família Pedaliaceae) foi realizado no campus de Jaboticabal, na estufa e laboratório molecular da Universidade Estadual Paulista (Unesp), Brasil. Isso teve como objetivo elucidar a diversidade entre algumas variedades de gergelim (Sesamum indicum L) na Nigéria usando parâmetros agro-morfológicos e marcadores moleculares de Repetições Simples Interespecíficas (ISSR). Oito variedades de gergelim: NCRIBEN-01M, NCRIBEN-02M, NCRIBEN-04E, NCRIBEN-05E, de semente preta, E8, Gujarat e Yandev-55 foram plantadas na estufa. Folhas foram coletadas 12 dias após o plantio e processadas para avaliação molecular. Além disso, cada variedade foi avaliada quanto a parâmetros agronômicos morfológicos em experimento em vaso na estufa, as variedades variaram na cor da casca da semente em quatro grupos: preta, marrom, marrom claro, branca e lobo foliar ovado na variedade E8. A altura da planta (cm) variou de 96,4±1,1 a 144,3±2,0, dias para 50% de floração e dias para maturação variaram de 55±1,0 a 68±1,0 e 91±1,0 a 130±2,0 dias, respectivamente. Os parâmetros que influenciam o rendimento variaram de 35±2,0 a 63±1,0 para cápsulas por planta, 52±2,0 a 76±2,0 para sementes por cápsula e 2,12±1,56 a 4,43±0,1 para peso de 1000 sementes (g). A matriz de componentes principais revelou que o PC1, que representou a maior variabilidade, estava principalmente relacionado a características relacionadas ao rendimento, como número de cápsulas por planta, número de ramos primários por planta e peso de 1000 sementes. O PC2 foi dominado por características relacionadas ao crescimento. O dendrograma de dissimilaridade dos genótipos de gergelim estudados, estabelecido usando agrupamento aglomerativo com coeficiente de 0,821, revelou três grupos. Esses resultados mostraram variabilidade nos caracteres de rendimento dessas variedades de gergelim estudadas. Onze iniciadores ISSR foram usados para análise de oito diferentes populações de gergelim da Nigéria. Os iniciadores mostraram perfis genômicos legíveis e reproduzíveis. Os 11 iniciadores amplificaram 472 bandas, das quais 228 (48,3%) foram polimórficas. O conteúdo de informação polimórfica (PIC) neste estudo com 11 genótipos de gergelim variou de 0,330 a 0,50, indicando a informatividade dos marcadores ISSR e sua relevância na discriminação das populações estudadas. Portanto, existe diversidade entre os genótipos de gergelim estudados. Estudos adicionais sobre diversidade genética de acessos de gergelim nigerianos usando marcadores ISSR com maior número de marcadores e genótipos irão revelar ainda mais seu grau de diversidade.
Diversidade genética para componentes de produção em gergelim (Sesamum indicum L.)
Keywords: Genetics; Molecular markers; Agriculture; Polymorphism